Dampak Perkembangan Uang Elektronik Terhadap Efektivitas Kebijakan Moneter Dalam Perspektif Sistem Ekonomi Islam - Cinta Rahmi; Iqbal Risyad Fadhillah; Adam Hamzah Danuri; Muhammad Rizky Ikhwan; Muhammad Irsyad (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The role of electronic money in increasing the effectiveness of monetary policy inIndonesia. In recent years, the use of electronic money in Indonesia has experienced significantgrowth, driven by the increasing adoption of digital technology and people's preference for noncash transactions. Electronic money has a positive impact on monetary stability throughincreasing transparency and accuracy of transaction data, which allows Bank Indonesia (BI) tomonitor and control inflation more effectively. In addition, the use of electronic moneystrengthens monetary policy transmission, where changes in interest rates can directly influencetransaction costs and consumption and investment behavior of the public. On the other hand,electronic money also contributes to the stability of the financial system by reducing the risk offraud and increasing financial inclusion, providing access to financial services to previouslyunreachable populations. Technological innovations in digital payments, such as QRIS, expandthe digital financial ecosystem and support transaction efficiency and security. This researchalso highlights the relevance of electronic money in the context of sharia economics, where theprinciples of transparency, accountability and social justice prioritized in sharia can be fulfilledthrough the use of electronic money. Thus, electronic money not only strengthens theeffectiveness of monetary policy but also supports financial system stability and financialinclusion in Indonesia, while also complying with sharia principles.Keywords: Electronic Money, Monetary Policy, Effectiveness